MathsHints: use Symbolab to solve linear algebra / Rafizah Kechil, Azlina Mohd Mydin and Wan Anisha Wan Mohammad - Kechil, Rafizah (Unit Penerbitan Dan Publisiti JSKM, 2023)
The learning process was further simplified by the quick development of technology and the simplicity of internet access. To further support teaching and learning, numerous websites and apps are created. The websites and apps created specifically for this purpose should be utilized to their greatest potential. Symbolab is one of the online resources for learning. In this article, we’ll go through how to use Symbolab to solve linear algebra-related problems.